PHYTOREMEDIATION OF THE HEAVY METALS COPPER, LEAD, CADMIUM, NICKEL AND COBALT USING SOME PLANT SPECIES OF THE ASTERACEAE FAMILY - I. M. Khalaf; A. T. Hameed; A. O. Talak; K. M. Nasir (مجلة الأنبار للعلوم الزراعية)
This study explores the complex dynamics of heavy metal accumulation in various plant species of the Asteraceae family, highlighting their role as natural mechanisms for environmental metal remediation. The process depends on soil composition, the bioavailability of heavy metals, and the presence of chelating agents. The research focused on the accumulation of copper , lead , cadmium , nickel , and cobalt  in selected plant species. Sonchus oleraceus demonstrated notable efficacy in reducing cadmium accumulation, recording the lowest concentration at 0.011mg/kg. Launaea nudicaulis proved to be a promising phytoremediation agent for lead, with the lowest concentration recorded at 7.55mg/kg. Bellis perennis showed strong potential in nickel absorption, with a minimum concentration of 0.32 mg/kg. Global permissible values confirmed the species' effectiveness in phytomediation for cobalt, which achieved the lowest concentration of 0.001mg/kg. Additionally, statistical analysis at the LSD 5% significance level highlighted notable differences, identifying the species as promising for copper remediation, with a minimum copper concentration of 11.32 mg/kg.    These findings emphasize the diverse capabilities of plants as natural agents in reducing the accumulation and spread of harmful heavy metals in the environment, providing valuable insights for sustainable mitigation of heavy metal pollution. The identified low accumulation values establish these plant species as promising candidates for environmentally friendly and sustainable remediation strategies. This calls for further research and practical implementation in polluted ecosystems. Future studies should delve deeper into understanding the observed differences and verify practical effectiveness these species through field studies and long-term monitoring of metal movement from plants to the environments and their cyclic tendencies